Long-term response of coastal macrofauna communities to de-eutrophication and sea level rise mediated habitat changes (1980s versus 2018) - Singer, Anja; Bijleveld, Allert I.; Hahner, Florian; Holthuijsen, Sander J.; Hubert, Krischan; Kerimoglu, Onur; Kleine Schaars, Loran; Kröncke, Ingrid; Lettmann, Karsten A.; Rittweg, Timo; Scheiffarth, Gregor; van der Veer, Henk W.; et al. (Frontiers in Marine Science, 2023)
Since the last decades, previous long-term Wadden Sea studies revealed significant changes in the abundance, biomass and spatial distribution of characteristic macrofauna communities in response to environmental changes and anthropogenic stressors. In this study, we performed statistical community analysis for the East-Frisian Wadden Sea (EFWS, southern North Sea) on two reference datasets across a period with severe climatic and environmental changes (1980s-2018). Therefore, historical macrofauna data from the Quantitative Sensitivity Mapping (1980s, SENSI 1) were reanalyzed and compared with data from the Synoptic Intertidal Benthic Survey (SIBES/SENSI 3) collected in 2018. Our results revealed significant quantitative and spatial changes in the characteristic macrofauna communities between the 1980s and 2018, most likely in response to de-eutrophication and sea level rise mediated habitat changes. Since the 1980s, the total number of taxa remained relatively stable (1980s: 90, 2018: 81), but the total abundance decreased by ca. -31% and the total biomass decreased by ca. -45%, particularly in the eastern regions of the study site probably due to de-eutrophication processes. Thereby, the mean abundances/m2 of ≥ -80% (1980s-2018) in the EFWS of several dominant species decreased: e.g. the gastropod Peringia ulvae, the polychaete Lanice conchilega and the bivalve Mya arenaria. In contrast, the mean abundance/m2 of one dominant species increased by ≥ +80% (1980s-2018): the invasive bivalve Ensis leei. The mean biomass [g/m2] of three dominant species decreased by ≥ -80% (1980s-2018): P. ulvae, L. conchilega and the amphipod Corophium volutator. In contrast, the mean biomass [g/m2] of one dominant species increased by ≥ +75% (1980s-2018): the polychaete Arenicola marina. In the western part of the EFWS, not only higher abundances of A. marina, but also of L. conchilega and P. ulvae were found in 2018, caused i.a. by sea level rise mediated decreasing mud contents and sand accretion on tidal flats. At the community level, the Oligochaeta/Heteromastus community increased in spatial distribution in the western EFWS in 2018 in the vicinity of increasing mussel/oyster beds.